Peran Lingkungan Sekolah Dalam Proses Pembelajaran Pendidikan Agama Hindu Dan Budi Pekerti Di SD Negeri 1 Canggu - I Made Surya Buana; Ni Komang Sutriyanti; Ni Nyoman Mariani (Jayapangus Press, 2019)
The school environment has an important role in the learning process of Hinduism and Pekerti in school, this is because when the school environment is not comfortable such as noise, the room is too glare, and there is not enough plants to make the school shady, then students will not concentrate in the process learning. When the school environment is comfortable, students will be happy and even motivated to learn. This study aims to determine (1) the role of the school environment in the process of learning Hinduism and Budi Pekerti at Canggu 1 State Elementary School. (2) To find out students' perceptions at SD Negeri 1 Canggu about the role of the school environment in the process of learning Hinduism and character traits. (3) To know the educational values ​​contained in the school environment that play a role in the process of learning Hinduism and character. The theories used to dissect the problem are: Education Theory, from Titib to dissect the first problem, Perception Theory, from Robbins to dissect the second problem, the Value Theory, from Louis O. Kattsoff (in rahayu) to dissect the third problem. The subjects of this study were Hindu religious education teachers and Hindu students at Canggu 1 Elementary School. Data collection method is by Observation Method, Interview, Literature, and Documentation. The data that has been collected is analyzed by qualitative descriptive analysis method with steps of reduction, data presentation, and conclusion drawing. The results of the study show (1) The role of the school environment in the Hindu and Pekerti learning process is to provide a means of learning through the physical environment of the school, and as a mental form of students through the school's social environment as well as students' self-development through the school's academic environment. (2) Students' perceptions at SD Negeri 1 Canggu about the role of the school environment in the process of learning Hinduism and character are students realize that the school environment is very instrumental in the learning process because schools provide facilities and infrastructure, methods that support the learning process, the existence of trees - trees that are shady and not noisy which makes students focus on learning. (3) Educational Values ​​contained in the School Environment that play a role in the Learning Process of Hinduism and Characteristic are the Value of Praise, Sradha Value and Cultural Value.